Information theoretical approach to detecting quantum gravitational corrections (vol 2025, 109, 2025) - Pourhassan, Behnam; Shi, Xiaoping; Wani, Salman Sajad; Al-Kuwari, Saif; Kazemian, Farideh; Sakalli, Izzet; Faizal, Mir (Springer, 2025)
[Abstract Not Available]